2008
DOI: 10.1016/j.precamres.2008.06.011
|View full text |Cite
|
Sign up to set email alerts
|

A deformed alkaline igneous rock–carbonatite complex from the Western Sierras Pampeanas, Argentina: Evidence for late Neoproterozoic opening of the Clymene Ocean?

Abstract: A deformed ca. 570 Ma syenite-carbonatite body is reported from a Crenville-age (1.0-1.2 Ca) terrane in the Sierra de Maz, one of the Western Sierras Pampeanas of Argentina. This is the first recognition of such a rock assemblage in the basement of the Central Andes. The two main lithologies are coarse-grained syen ite (often nepheline-bearing) and enclave-rich fine-grained foliated biotite-calcite carbonatite. Samples of carbonatite and syenite yield an imprecise whole rock Rb-Sr isochron age of 582 ± 60 Ma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 54 publications
2
33
0
1
Order By: Relevance
“…2). Neoproterozoic metaigneous rocks of Syenite-Carbonatite Complex (Casquet et al 2008b) and dykes of A-Type Granitoids are additionally exposed in Sierra de Maz and del Espinal (Baldo et al 2008;Colombo et al 2009). The tectono-metamorphic events affecting the Maz, El Taco, and El Zaino groups, based mainly on Kilmurray (1970) and Kilmurray and Dalla Salda (1971), and their isotopic constraints are shown in Tables D and E (Electronic Supplementary Material).…”
Section: Sierra De Maz Del Espinal and Toro Negro Areasmentioning
confidence: 99%
“…2). Neoproterozoic metaigneous rocks of Syenite-Carbonatite Complex (Casquet et al 2008b) and dykes of A-Type Granitoids are additionally exposed in Sierra de Maz and del Espinal (Baldo et al 2008;Colombo et al 2009). The tectono-metamorphic events affecting the Maz, El Taco, and El Zaino groups, based mainly on Kilmurray (1970) and Kilmurray and Dalla Salda (1971), and their isotopic constraints are shown in Tables D and E (Electronic Supplementary Material).…”
Section: Sierra De Maz Del Espinal and Toro Negro Areasmentioning
confidence: 99%
“…local postmagmatic dextral shear zones, can be explained by the change of the plate boundary from convergent to a transform boundary. Rapela et al (2007) and Casquet et al (2008) suggested that the Puncoviscana Formation was probably a fore-arc sedimentary sequence that had developed on the southern margins of the Kalahari craton. The collision of the Western Sierras Pampeanas Terrane and the Arequipa craton against the Kalahari craton was followed by the displacement of the Puncoviscana Formation and higher-grade metamorphic equivalents along dextral shear zones (Martino 2003) up to its present position facing the Río de la Plata craton.…”
Section: Geological Settingmentioning
confidence: 99%
“…Different geological settings like passive or active margin, as well as autochthony or allochthoneity of the involved units, were discussed for the Neoproterozoic to early Palaeozoic evolution of the metasedimentary units of the Eastern Sierras Pampeanas and the Cordillera Oriental, (e.g. Ramos 1988;Bahlburg 1990;Astini et al 1995;Pankhurst and Rapela 1998;Rapela et al 1998Rapela et al , 2007Bock et al 2000;Lucassen et al 2000;Zimmermann and Bahlburg 2003;López de Luchi et al 2003;Schwartz and Gromet 2004;Steenken et al 2004Steenken et al , 2006Zimmermann 2005;Rapela et al 2007;Schwartz et al 2008;Adams et al 2008;Casquet et al 2008;Drobe et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…and related metaclastic rocks to the south, and Gondwanan sources in South Africa, led some authors to propose an alternative model in which the Puncoviscana sediments were deposited in a trough marginal to the Kalahari craton and later emplaced against the western margin of the Rio de la Plata craton through a lateral strikeslip displacement (Rapela et al, 2007;Casquet et al, 2008;Drobe et al, 2009Drobe et al, , 2011Siegesmund et al, 2010). Based on Sm-Nd isotopic data and zircon provenance patterns, Collo et al (2009) proposed that the Puncoviscana Fm.…”
Section: Introductionmentioning
confidence: 84%
“…In alternative models proposed by Rapela et al (2007), Casquet et al (2008), Drobe et al (2009 and references therein, the Puncoviscana Fm. was a fore-arc sedimentary sequence that developed on the margin of the Kalahari craton.…”
mentioning
confidence: 99%